Thymidine kinase 1 silencing retards proliferative activity of pancreatic cancer cell via E2F1‐TK1‐P21 axis. (20th December 2017) - Zhu, Xiaole; Shi, Chenyuan; Peng, Yunpeng; Yin, Lingdi; Tu, Min; Chen, Qiuyang; Hou, Chaoqun; Li, Qiang; Miao, Yi
Abstract: Objectives: Thymidine kinase 1 (TK1) is one of the salvage enzymes engaged in the synthesis of DNA. Although a pro‐carcinogenetic role of TK1 has been reported in various types of cancers, its role in pancreatic ductal adenocarcinoma (PDAC) is still unknown. The study is aimed to elaborate the function of TK1 in PDAC and the potential mechanisms in the following study. Materials and methods: TK1 expression was analysed by immunohistochemistry, real‐time PCR and Western blot, and its relationship with clinicopathological characteristics of PDAC patients was further investigated. To verify the function of TK1 and potential mechanism, TK1 siRNA was used to transfect PDAC cells and performed a series of assays in cell and animal models. Results: The level of TK1 expression was higher in cancerous tissues compared with matched adjacent tissues. TK1 overexpression was associated with progression of PDAC and poor prognosis. Knockdown of TK1 could suppress cell proliferation via inducing S phase arrest mediated by upregulation of P21. Further mechanism investigation suggested that transcription factor E2F‐1 could directly regulate the TK1 and promote tumour proliferation. Conclusions: The results suggested that TK1 might be involved in the development and progression of PDAC by regulating cell proliferation and show that TK1 may work as a promising therapeutic target in patients with PDAC.